2013
DOI: 10.1039/c2ob27163j
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity assessment of chalcones by a kinetic thiol assay

Abstract: The electrophilic nature of chalcones (1,3-diphenylprop-2-en-1-ones) and many other α,β-unsaturated carbonyl compounds is crucial for their biological activity, which is often based on thiolmediated regulation processes. To better predict their biological activity a simple screening assay for the assessment of the secondorder rate constants (k 2 ) in thia-Michael additions was developed.Hence, a clear structure-activity relationship of 16 differentially decorated hydroxy-alkoxychalcones upon addition of cystea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 19 publications
0
66
0
Order By: Relevance
“…9,10,26 In this study, a 96-well microtiter plate-based screening system was used in a thiol reactivity screen for a simple and quick determination of binding to cysteamine, dithiothreitol, 2-mercaptoethanol, GSH, and cysteine. 27 These reports led us to examine the reactivity of biliatresone toward EVK, one of the more reactive compounds studied.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,26 In this study, a 96-well microtiter plate-based screening system was used in a thiol reactivity screen for a simple and quick determination of binding to cysteamine, dithiothreitol, 2-mercaptoethanol, GSH, and cysteine. 27 These reports led us to examine the reactivity of biliatresone toward EVK, one of the more reactive compounds studied.…”
Section: Discussionmentioning
confidence: 99%
“…95 The second order rate constants for the addition of cysteamine, a model protein surface thiol due to its pK a of 8.3, were calculated from the rates observed under pseudo-first order conditions (40 μM chalcone, 480 to 20000 μM cysteamine) by monitoring the decrease in UV absorbance of the enone peak between 350 and 375 nm. 96 These reactions were performed in a solution of Tris-HCl buffer (pH = 7.4) and ethylene glycol (1:4), which contained 2 mM EDTA to prevent thiol oxidation, and a 12-500 fold excess of cysteamine. 96 A chalcone bearing a 2'-hydroxy group ( 244 ) reacted the fastest with cysteamine (k 2 = 5.1 M −1 s −1 ) and a chalcone with no aromatic substituents ( 243 , R = H) reacted the second fastest (k 2 = 3.0 M −1 s −1 ).…”
Section: αβ-Unsaturated Ketones (Enones)mentioning
confidence: 99%
“…96 A chalcone bearing a 2'-hydroxy group ( 244 ) reacted the fastest with cysteamine (k 2 = 5.1 M −1 s −1 ) and a chalcone with no aromatic substituents ( 243 , R = H) reacted the second fastest (k 2 = 3.0 M −1 s −1 ). 96 All other chalcones with hydroxy and alkoxy substituents at various positions on the aromatic rings reacted with a k 2 between 0.1 and 1 M −1 s −1 , and it was observed that a 2'-hydroxy group generally increased the rate of thiol addition while 2'-alkoxy groups reacted more slowly. 96 When 2'-hydroxy groups were present, cyclization of the pendant amine from cysteamine into the ketone led to formation of the 1,4-tetrahydrothiazepine 245 , 96 which has also been reported to occur with unsaturated aldehydes as discussed later (Scheme 13).…”
Section: αβ-Unsaturated Ketones (Enones)mentioning
confidence: 99%
“…While the SAR described above is consistent with our model of M0 binding, these results are also notably inconsistent with the behavior expected if these compounds were simply carrying out thia-Michael additions. Kinetic studies using a model thiol (cysteamine) demonstrate that the presence of the 6’-methoxy group decreases reactivity, and the 2’-hydroxy group increases reactivity [84]. Through the comparisons above, we find that the most potent compounds for inhibition of Mcl-1 correspond to those expected to be least reactive, further implying that the inhibition we observe is not due to reactivity of these compounds with Mcl-1’s unpaired cysteine sidechain.…”
Section: Resultsmentioning
confidence: 67%